Peran Pemerintah Daerah dalam Meningkatkan Mutu Pendidikan pada Masa Pandemi Covid-19 - Wulandari Wulandari (University Of Bengkulu Law Journal, 2022)
During the current Covid-19 Pandemic, it is challenging to put into practice the meaning of quality education. In the midst of the COVID-19 pandemic, the Ministry of Education, Culture, Research, and Technology's policy is important to note because it will affect Indonesian education. Within the confines of the university, this daring educational strategy is implemented from the elementary through the graduate levels. During the Covid-19 pandemic, it is becoming increasingly difficult to provide every Indonesian citizen with a decent education, and there are numerous obstacles to overcome. During the Covid-19 pandemic, the purpose of this article is to investigate and ascertain the role that local governments played in efforts to raise the standard of education. This study is a normative juridical research (das sollen) with the objective of determining the applicable principles and philosophical foundations (dogmas or doctrines) of positive law, specifically invitation regulations pertaining to the role of local governments, particularly in enhancing the quality of education during the COVID-19 pandemic. The study found that the regional government adapts the central government's policies to deal with the COVID-19 pandemic to regional conditions, needs, and capabilities and follows through on those policies. Through its policies, the local government offers suggestions for various learning models that teachers can use as guidelines to implement in the classroom.